2019
DOI: 10.1088/1755-1315/276/1/012054
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Guava on the Improvement of Lipid Profile in Hypercholesterolemic Rats

Abstract: Red guava is a fruit species with high vitamin C content and the highest fibers, in particular, soluble fiber (pectin) among tropical fruits and cereals. The soluble fiber is hypocholesterolemic in the body. Therefore, it has the potential to reduce cholesterol content. This study aimed to assess the potential of red guava in reducing cholesterol content in hypocholesterolemic rats. This study applied a pure experiment using a randomized pretestposttest group design on hypocholesterolemic Sprague Dawley rats. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…In its composition, it is possible to find several bioactive compounds These bioactive nutrients play significant roles in several health problems related to lifestyle diseases, such as diabetes (type 2), cardiovascular disease, several cancer types and obesity. As regards the hypocholesterolemic properties of guava, Maryanto and Marsono, [140] carried out a study to assess the potential of red guava in reducing cholesterol content in hyper-cholesterolemic rats. They found that red guava intake significantly reduced the contents of total cholesterol (32%), low-density lipoprotein cholesterol (43%), and triglyceride (18%).…”
Section: Guavamentioning
confidence: 99%
“…In its composition, it is possible to find several bioactive compounds These bioactive nutrients play significant roles in several health problems related to lifestyle diseases, such as diabetes (type 2), cardiovascular disease, several cancer types and obesity. As regards the hypocholesterolemic properties of guava, Maryanto and Marsono, [140] carried out a study to assess the potential of red guava in reducing cholesterol content in hyper-cholesterolemic rats. They found that red guava intake significantly reduced the contents of total cholesterol (32%), low-density lipoprotein cholesterol (43%), and triglyceride (18%).…”
Section: Guavamentioning
confidence: 99%
“…This condition reinforced the suspect that EBP J30 flour and food bar could reduce the risk of atherosclerosis. The decrease in AIP value indicated the decreased levels of pro-atherogenic lipoproteins (triglycerides and LDL) and the increased anti-atherogenic (HDL) [35].…”
Section: E Atherogenic Index Plasmamentioning
confidence: 99%
“…Guava ( Psidium guajava L.) is popular in tropical countries, being consumed fresh or processed into juices, frozen pulp, jams, and pie fillings. Besides its commercial value, it has been reported that this fruit present health‐promoting effects such as the mitigation of oxidative stress‐induced damage to human dermal fibroblasts (Alvarez‐Suarez et al, 2018), cytotoxicity against human breast adenocarcinoma cells (Dos Santos et al, 2018), and reduction of LDL cholesterol in rats (Maryanto & Marsono, 2019).…”
Section: Introductionmentioning
confidence: 99%